Analysis of the micro-cracking behaviour of carbon fibre reinforced flywheel rotors considering residual stresses. (15th November 2018) - Koch, I.; Just, G.; Otremba, F.; Berner, M.; Gude, M.
Abstract: The main challenge in today's power grid management is the inclusion of renewable energy sources with inconstant energy production such as wind and solar plants and modern high technology fabrication or electric transportation with their uneven power consumption. For that purpose energy storage systems, such as high efficiency flywheels, with extraordinary cycle stability and charging-discharging rates are needed. Here carbon fibre reinforced composites play an important role as rotor material. In this study the cracking behaviour of helical layers of a cylindrical flywheel rotor is analysed under consideration of fabrication induced residual stresses and their viscoelastic reduction over long term storage. Based on static and fatigue experiments with crack counting inspections a finite fracture model is identified and calibrated for modelling the damage behaviour of flywheel rotors under cyclic loading.